Association of global ultraviolet radiation with the incidence of aneurysmal subarachnoid hemorrhage - Mirbagheri, Andia; Rinkel, Gabriel J. E.; Berneburg, Mark; Etminan, Nima (Neurosurgery, 2025)
BACKGROUND AND OBJECTIVES: Inflammation is a key pathomechanism for growth and rupture of intracranial aneurysms. Anti-inflammatory mechanisms may reduce rupture of intracranial aneurysms and the incidence of aneurysmal subarachnoid hemorrhage (SAH). Ultraviolet (UV) radiation from sunlight exposure induces systemic anti-inflammatory responses through immunosuppressive mechanisms. We studied whether SAH incidence is associated with UV radiation. METHODS: Global SAH incidence, time trends, and regional differences from 32 countries were linked to UV radiation data from the Tropospheric Emission Monitoring Internet Service. Odds between low vs high UV exposure and SAH incidence were calculated. Correlation analysis was performed using R (R 4.1.2). - RESULTS: - SAH incidences ranged from 1.3 to 27 per 100 000 patient-years (p-y) and UV index from 1.76 to 11.27. The correlation coefficient (rho) between SAH incidence and UV index was −0.48 (P = .012). SAH incidence was highest in Japan (13.7-27.9 p-y) with an UV index 6.28. UV index was highest in Chile 11.27 with a lower SAH incidence (3.8-4.8 p-y). The lowest UV index 1.76 was seen in Iceland with higher SAH incidence (9.8 p-y).Within Europe, regions with higher UV indices reported lower SAH incidences (Northwest Europe: SAH incidence p-y 8.61/UV index 2.85; Southeast Europe: SAH incidence p-y 7.37/UV index 4.65) with a significant inverse correlation (rho = −0.68, P = .004) and not a significant correlation between non-European countries (rho = −0.43, P = .19). Low exposure of UV radiation in global regions predicted higher than median incidences of SAH with an odds ratio 5.13 (95% CIs 1.02-31.5). CONCLUSION: The incidence of SAH is inversely associated with UV radiation. Further studies should assess the actual UV exposure in relation to SAH incidence and potential biological explanations for the relation we found.
Online veröffentlicht: 1. Juli 2024
Gesehen am 13.05.2025